Olive response to potassium applications under different water regimes and cultivars - Ferreira, Isabel Q. (2018)
Although potassium (K) is a macronutrient few studies have evaluated the response of olive tree to K fertilization. In this work results of two ﬁeld and two pot K fertilizer experiments are presented. One of the ﬁeld trials was conducted in a commercial young olive grove. The second was conducted in a plantation purposely established for this study. In the two ﬁeldand theﬁrst potexperiment,theK supply was the single variation factor. The second pot experiment was arranged as a factorial with two K rates, two water regimes and two cultivars (‘Arbequina’ and ‘Cobranc¸osa’). K supply did not increase olive tree growth or yield. Accumulated olive yield in the ﬁrst ﬁeld experiment, for instance, varied from 2.46 and 2.84 kg tree-1, respectively in K treated and untreated plants. K supply increased the shoot/root ratio (1.6–2.0 from the control to the most fertilized treatment) and the concentration of K in roots (2.9–11.2 g kg-1) to a greater extent than in leaves (7.0–11.9 g kg-1), suggesting that shoots are a priority sink for K and roots may store the nutrient as a reserve. Plant water status and chlorophyll a ﬂuorescence were not signiﬁcantly affected by K applications. Plants suffering from water stress yielded less phytomass (40.2–56.4 g pot-1, respectively in control and well-watered plants) and showed higher K concentrations in leaves (14.2–11.6 g kg-1) and lower in roots (4.9–6.8 g kg-1) which is probably due to the reduction of K uptake from the dry soil. ‘Cobranc¸osa’ appeared to be more tolerant to water stress than ‘Arbequina’. These experiments showed a poor response of olive tree to K fertilization. Considering that K is usually applied by farmers every year, it seems that further studies on K fertilizationin olive are needed in order to adjust K fertilizer rates to crop needs.